Thermotropic MIDA Boronates as a Case Study for the Role of Dipolar Interactions in Liquid Crystalline Self‐Assembly. Issue 17 (28th February 2017) - Wöhrle, Tobias; Gündemir, Rafet; Frey, Wolfgang; Knecht, Friederike; Köhn, Andreas; Laschat, Sabine
Abstract: A series of MIDA ( N ‐methylimino diacetic acid) boronates carrying 4‐alkoxy, 3, 4‐bisalkoxy, or 3, 4, 5‐trisalkoxyphenyl substituents were synthesized and their mesomorphic properties characterized by differential scanning calorimetry (DSC), polarizing optical microscopy (POM), and X‐ray diffraction (XRD) techniques such as small‐ and wide‐angle X‐ray scattering (SAXS and WAXS, respectively). Most derivatives were liquid crystalline. In the case of mono‐ and bisalkoxy‐substituted derivatives, C6 chains already induced smectic A (SmA) mesophases despite the bulky MIDA head group. With increasing chain length, columnar hexagonal (Colh ) phases replaced SmA phases in the disubstituted series. Quantum chemical calculations on a series of MIDA boronates show that the B−N bond is a dative bond with a positive charge on the boron atom and negative charges on the nitrogen and oxygen atoms. In addition, no π‐interaction between the aryl moiety and B−N bond was found, thus the mesogenic unit is electronically decoupled from the MIDA head group. These theoretical findings were supported by IR and Raman spectra as well as by asingle crystal structure analysis of 4‐ethoxyphenyl MIDA boronate. Calculations of the electrostatic potential of the MIDA boronate reveal a special polarity pattern that can support the formation of a two‐dimensional network and is likely to explain the liquid crystalline self‐assembly. The absence of any electronic cross‐talk between the MIDA head group and B‐aryl or B‐alkyl substituents allows the efficient tailoring of the mesophase type through variation of the substituents. Abstract : In contrast to the non‐mesomorphic aryl boronic acids and diethanolamine boronates, MIDA boronates form smectic or columnar mesophases, which was rationalized by strong dipolar interactions according to quantum chemical calculations.